Corneal Collagen Cross Linking - Sinjab, Mazen M.; Cummings, Arthur B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides comprehensive coverage of corneal collagen cross-linking (CXL), a major management modality for keratoconus and ectatic corneal disorders. All aspects are covered, including refractive and non-refractive surgery indications, models of application, safety, efficacy, performance, outcome measures, evidence of CXL, complications, contraindications, use in children, and controversies. The discussion reflects the considerable progress that has been made in understanding of the modality since its development in the late 1990s. Detailed attention is paid to new concepts, changing surgical techniques and indications, the latest evidence-based science and research, and the future of CXL. Guidance is also provided on the use of CXL in combination with other modalities, such as LASIK, PRK, intracorneal ring implantation and others. The text is accompanied by numerous high-quality color illustrations. Corneal Collagen Cross Linking will provide the reader with a sound grasp of the technique and its use and will hopefully also serve as a stimulus to further research and advances.
Basics of Corneal Collagen Cross Linking -- Indications -- Models of Application -- Outcome and Efficacy Measures -- Evidence of CXL -- Complications -- Contraindications -- CXL in Children -- Controversies in CXL.
Keywords: Medicine; Ophthalmology; Medicine & Public Health; Ophthalmology